2013
DOI: 10.1001/jamasurg.2013.2132
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Overtriage

Abstract: The incidence of secondary overtriage in our rural trauma center is 26%, with head and neck injuries being the most common reason for transfer. Costs for transportation and additional evaluation for such a significant percentage of patients has important resource utilization implications. Effective regionalization of rural trauma care should include methods to limit secondary overtriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 14 publications
(21 reference statements)
2
55
1
Order By: Relevance
“…There were no other studies in the literature utilizing our definition, which we believe better allows the study of the decision that the treating physician at the initial facility must make of whether to transfer the patient. We confirm the previous finding that the pediatric population seems to be more often overtriaged than the adults [10]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were no other studies in the literature utilizing our definition, which we believe better allows the study of the decision that the treating physician at the initial facility must make of whether to transfer the patient. We confirm the previous finding that the pediatric population seems to be more often overtriaged than the adults [10]. …”
Section: Discussionsupporting
confidence: 92%
“…Most definitions include a discharge time within 24–48h, with or without limiting the ISS to exclude the more severe injuries, and with or without excluding patients who had an operation. Most studies have been from single institutions comparing the rate of secondary overtriage using the total number of incoming transfers to that institution as the denominator [1, 9, 10]. An exception to the single institution studies was one done by Osen, in which selected all transferred trauma patients form the National Inpatient Sample, and they found the secondary overtriage rate to be 6.9% [11].…”
Section: Introductionmentioning
confidence: 99%
“…14,15,20 In keeping with this, injury patterns were strongly predictive of SO in our study. Head and neck injuries were the most common cause of SO in a study by Sorensen, 7 whereas orthopedic injuries and neurologic trauma were common reasons for overall transfer in other studies. 3,20 Interestingly, neurosurgical, orthopedic, spine, and facial surgical services at nontrauma centers have been associated with increased risk of “undertriage” in Medicare patients at some centers.…”
Section: Discussionmentioning
confidence: 88%
“…This differs from the findings of other authors, who reported no difference in payer status mix among patients transferred to a level 1 trauma center versus those directly admitted to the center 20 but is in accordance with other studies showing increased risk of SO among patients with Medicare or Medicaid. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation